2013
DOI: 10.1093/ntr/ntt016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on Olfactogustatory Incentives: Preference, Palatability, and Operant Choice Tests

Abstract: The use of additives in tobacco may capitalize on the incentive motivational properties of tastes and scents such as mint (menthol), vanilla, and strawberry. These incentives are intended to increase tobacco experimentation, but their salience may also be enhanced by the incentive amplifying effects of nicotine (NIC). The goal of the present studies was to investigate the potential interaction between the incentive amplifying effects of NIC and gustatory incentives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
(39 reference statements)
0
17
1
Order By: Relevance
“…However, our anecdotal observation confirmed that when two rats poke their noses into the divider at the same time, they were always at the same hole. Nicotine is known to enhance the effect of nonpharmacological rewards (Palmatier et al 2005; Palmatier et al 2013). Our data suggest that nicotine enhances social reward.…”
Section: Discussionmentioning
confidence: 99%
“…However, our anecdotal observation confirmed that when two rats poke their noses into the divider at the same time, they were always at the same hole. Nicotine is known to enhance the effect of nonpharmacological rewards (Palmatier et al 2005; Palmatier et al 2013). Our data suggest that nicotine enhances social reward.…”
Section: Discussionmentioning
confidence: 99%
“…Disparate appetitive stimuli also have been shown to be subject to NIC enhancement, including gustatory stimuli, sucrose-paired stimuli, drug-paired stimuli, and social interactions. 9,12,16,21 Moreover, although the number of stimulus-context pairings differed between FS and LiCl conditioning, NIC enhanced avoidance behavior supported by both aversive stimuli. Finally, the reinforcement-enhancement effect of NIC was present at both NIC doses, consistent with previous results.…”
Section: Discussionmentioning
confidence: 95%
“…[9][10][11][12] Alternatively, NIC might promote behavior that results in the removal of a potentially aversive stimulus. 13 We attempted to resolve this issue by utilizing two distinct stimuli known to be aversive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the smoker, this means that other reinforcers ongoing while smoking (i.e., self-administering nicotine) may be more potent than when not smoking (see Caggiula et al, 2009 for a review). In laboratory studies, this effect is shown by increased operant responding in rodents for a variety of rewards such as food (Barrett and Bevins, 2013; Palmatier et al, 2013) and visual stimuli (Donny et al, 2003; Barrett and Bevins, 2012) after nicotine exposure. In addition, this effect is not specific to non-human animals, as increased levels of responding for music has been shown in humans after nicotine exposure (Perkins and Karelitz, 2013).…”
Section: Introductionmentioning
confidence: 99%